Prospecção geofísica de água subterrânea na região da Picada Grande, Caçapava do Sul – RS - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The southern region of the country historically suffers water scarcity, largely due to droughts and annual dry spells. In this context, this study aims to provide subsidies to identify potential underground aquifers in the Picada Grande region, Caçapava do Sul, RS. The study area includes igneous, sedimentary, and metamorphic rocks, along with a significant presence of structural lineaments. The research utilized satellite imagery to identify lineaments, followed by geological and geophysical field surveys using electrical profiling technique, with the dipole-dipole array. Data processing was carried out using Res2Dinv software, integrating field-acquired altitude data to create a 2D resistivity model with topography. Interpretation of the geophysical sections revealed regions with low resistivity values ranging from 10 to 50 ohm.m, as well as areas with high resistivity ranging from 1000 to 1600 ohm.m, at varying depths. Correlating these findings with field geological data and remote sensing showed that regions where geological structures were detected typically exhibited low resistivity values. Based on this, two potential well sites near geological structures along line MV-01 and one on line MV-02 were selected for further consideration. This study underscores the importance of integrating geological and geophysical data for groundwater prospecting, illustrating its application in identifying areas favorable for groundwater occurrence in a community facing seasonal water scarcity in the interior of Caçapava do Sul.
Keywords: Aquífero; Lineamentos estruturais; Eletrorresistividade; Caminhamento elétrico; Dipolo-dipolo; Aquifers; Structural lineaments; Geophysical prospecting; Electroresistivity; Electrical profiling technique; Dipole-dipole; CNPQ::CIENCIAS EXATAS E DA TERRA